Combining internal and external inputs for sustainable intensification - Ruben, Ruerd; Lee, David R. (International Food Policy Research Institute, 2000)
Farmers and local development organizations around the world use and promote a variety of technologies to increase food production. But the high cost of inorganic fertilizers and other agrochemicals often drives farmers to rely on locally available resources instead of purchased, externally produced inputs. Well-targeted agricultural research can help reduce dependence on external inputs through work on problems such as pest resistance, drought tolerance, soil salinity, and nitrogen fixation.